Clinical Characteristics and Surgical Outcomes of Right Heart Myxoma and Its Comparison with Left Heart Myxoma: A Single-Center Retrospective Study - Yanyi Liu; Xin Li; Zhuang Liu; Yiyao Jiang; Chenghao Lu; Shenglin Ge; Chengxin Zhang (Anatolian Journal of Cardiology, 2023)
Background: Cardiac myxomas are commonly located in the left atrium but rarely affect the right side of the heart. We retrospectively analyzed 28 patients receiving surgical treatment for right heart myxomas at our center and aimed to summarize the clinical features and surgical outcomes of right heart myxomas.